Evaluation of the Quality of Academic Supervision of Graduation Research through the Online Portal of the Deanship of E-Learning and Distance Education at the University of Science and Technology in Yemen - Aljaji, Raja (IIUM Journal of Educational Studies, 2023)
The aim of this study is to evaluate the quality of academic supervision for graduation research through the online portal in the Deanship of E-Learning and Distance Education at the University of Science and Technology in Yemen. This was done by identifying the criteria for quality of academic supervision and analyzing the content of conversations between students and supervisors in the online portal to determine the extent to which those criteria were met. The study employed a mixed approach and used content analysis to analyze electronic conversations based on four criteria that describe the quality of academic supervision for graduation research: development of research skills, clarity of instructions, communication flexibility, and continuity. The study population consisted of 206 students who completed their graduation research in the first and second semesters of the academic year 2022-2023. They were enrolled in the online portal in five academic departments (Islamic Studies and Arabic Language, Administrative Sciences, Accounting and Finance, Sharia and Law, Humanities and Social Sciences). A 20% proportion was selected from the population to be the study sample, consisting of 41 male and female students. Among the key findings of the study were that the quality of academic supervision was average, with the Department of Accounting and Finance performing the best. The criterion of "development of research skills" was the weakest in terms of achievement, despite being the most important and prioritized according to the course description, with an achievement rate of 46%. The criterion of "communication flexibility" achieved the highest percentage of 85.6% among all criteria, followed by "clarity of instructions" with a rate of 77.8%, and "continuity of communication" with a rate of 70%.